Audit of Information Tecnology Governance at BKKBN Riau Province using the 2019 Cobit Framework - Fandi, Ridho Arif; Jazman, Muhammad; Fronita, Mona; Saputra, Eki (Sistemasi: Jurnal Sistem Informasi, 2024)
The implementation of Information Technology in government agencies has been used to enhance management processes and productivity, making them more accurate and faster, which leads to an improvement in the organization's ability to achieve Governance Management Objectives (GMO) and Good Corporate Governance. The BKKBN of Riau Province has implemented Information Technology in its execution in the form of SIGA (Sistem Informasi Keluarga) and Srikandi (Sistem Informasi Kearsipan Dinamis Terintegrasi). BKKBN is a non-ministerial government agency tasked with population control through family planning and prosperous family programs. Cobit 2019 is an international standard for assessing IT governance and management within companies, which also provides solutions for improving those issues.This research aims to measure the level of organizational capability in IT implementation. The results of the analysis of the Design factor objective APO-09-Managed Service Agreements and DSS-01 Managed Operations have the highest importance value, which is 60. The measurement results for APO-09 reached 74% at capability level 3 with the status of Largely Achieved or not yet achieved, while DSS-01 reached a value of 79% at level 3, which means both process objectives are at level 2, indicating that the process activities have achieved their goals by performing a number of basic but complete activities. With these results, both process objectives require improvement based on recommendations formulated from the gap analysis to achieve the expected capability.